Research progress on strengthening mechanism and industrial application of CO2 mineralization technology for coal electricity solid waste - Cao, Xinyue; Wang, Qingxiang; Li, Mengyang; Ma, Chicheng; Wang, Shilin (Results in engineering, 2025)
•Reviews major CO2 mineralization enhancement methods.•Compares direct and indirect mineralization technologies in thermodynamics, kinetics, and other aspects.•Studies mineralization characteristics of three typical coal electricity solid wastes and explores multi-dimensional strengthening mechanisms.•Proposes an innovative industrial application framework integrating efficiency enhancement, ecological sustainability, and intelligent regulation.•Identifies key issues in industrializing CO2 mineralization and future research directions. With the deepening of industrialization, the huge consumption of coal energy has led to a surge in CO2 emissions, posing a serious threat to the global environment. The CO2 mineralization technology of coal electricity solid waste can convert CO2 into stable carbonate by the chemical reaction, which provides an important path for the collaborative realization of carbon emission reduction and solid waste recycling. This paper systematically reviews the reaction mechanism, raw material characteristics, and multi-dimensional strengthening strategies of CO2 mineralization technology for coal electricity solid waste. It deeply analyzes the direction of its industrial application bottleneck and optimization suggestions. Firstly, this paper briefly discusses the current mainstream CO2 mineralization raw materials, processes, and mechanisms and based on the perspective of thermodynamics and kinetics, compares the characteristics and corresponding reaction mechanisms of direct and indirect mineralization technologies, analyzing the influencing factors and technical advantages of different technology routes. Secondly, this study investigates the mineralization characteristics of three coal-derived wastes, reveals the multi-dimensional strengthening mechanisms of temperature regulation, liquid-solid ratio optimization, leaching agent selection, and pH swing technology, highlights critical challenges in current methodologies, and suggests promising avenues for future research. Finally, given the current industrial implementation challenges of CO2 mineralization technology using coal electricity solid wastes, this study proposes an innovative development framework that integrate efficient enhancement, ecological sustainability, and intelligent regulation. This study provides theoretical support and practical reference for the engineering transformation and multi-scenario application of CO2 mineralization technology of coal electricity solid waste